Poka-Yoke Method Implementation in Industries: A Systematic Literature Review - Rommy Febri Prabowo; Siti Aisyah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2020)
The use of this poka-yoke approach is influential in preventing human error and can increase machine utilization and efficiency levels, to reduce breakdowns and product defects. The fundamental principle of the successful implementation of Poka Yoke is when everyone in the organization places quality attributes as important. This study aimed to determine the level of success of the Poka-Yoke method in improving quality in the manufacturing and service industries. The technique used is to conduct a review of research papers. The only 33 journals (around 69%) use the implementation of Poka-Yoke. And 15 journals (31%)  as a review of the method. The method used is to review research papers that consistently apply Poka-Yoke. The obtained six similarities in the function and purpose of improvisation from the application of the poka-yoke method, namely reducing defects, improving the design, saving costs, increasing productivity, reducing losses, and saving time. Poka-Yoke method can improve the quality of the manufacturing and service industry in future research.